Choroidal Thickness and Ametropia in Children: A Longitudinal Study. Issue 6 (8th November 2017) - Fontaine, Marine; Gaucher, David; Sauer, Arnaud; Speeg-Schatz, Claude
Purpose: To determine the relationship of subfoveal choroidal thickness (ChT), refraction, and axial length in children, and evaluate the evolution of subfoveal ChT with time in myopic versus nonmyopic eyes. Methods: A total of 229 eyes of 115 children aged 2 to 16 years were included in the study. Refraction under cycloplegia, axial length, and subfoveal ChT were measured at baseline with comparative investigations at 15 months follow-up. Results: The probability for the subfoveal ChT to be thinner in myopic children compared to nonmyopic children was 0.9999. We found a relation between subfoveal ChT and axial length. At 15 months follow-up, subfoveal ChT was found to have increased in the nonmyopic eyes, but decreased in myopic patients. Conclusions: A number of studies have already shown the choroid to play an important role in the process of emmetropization. We found that ChT had a different evolution in myopic children compared to nonmyopic children. A thinner choroid may predict the onset, or progression, of myopia. Further studies, with longer follow-up, are necessary to confirm this hypothesis.